Attitudes to love and marriage in poetry by women of the Romantic Period : a thesis presented in partial fulfilment of the requirements of Master of Arts in English at Massey University - Jones, Rachel Anne (Massey University, 1994)
This thesis examines the little-known poetry of the women poets writing during the Romantic Period in Britain. In particular, it focuses on attitudes to love and marriage expressed in their poetry, with a view to showing how women poets were confined by their society's ideology and how this affected the content of their poetry. The thesis focuses on poems that deviate from the ideologically "appropriate" representations of love and marriage and attempts to identify the strategies by which the women managed to express conventionally unacceptable thoughts. Particular attention is paid to the work of the two leading women poets of the period, Felicia Hemans and Letitia Landon.
Keywords: 18th century English literature; 19th century English literature; Women authors; History and criticism; Women in literature